2021
DOI: 10.1080/2162402x.2021.1965319
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol lipase deficiency in the tumor microenvironment slows tumor growth in non-small cell lung cancer

Abstract: Monoacylglycerol lipase (MGL) expressed in cancer cells influences cancer pathogenesis but the role of MGL in the tumor microenvironment (TME) is less known. Using a syngeneic tumor model with KP cells (Kras LSL-G12D /p53 fl/fl ; from mouse lung adenocarcinoma), we investigated whether TME-expressed MGL plays a role in tumor growth of non-small cell lung cancer (NSCLC). In sections of human and experimental NSCLC, MGL was found in tumor cells and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 89 publications
3
37
0
Order By: Relevance
“…MAGL plays a major role in the endocannabinoid metabolism in addition to its lipolytic functions. MAGL provides a large pool of arachidonic acid (AA), from which pro-inflammatory prostaglandins are generated 41 . 2-AG, CB1/CB2 receptors and MAGL are key regulators of the endocannabinoid system involve in regulation of various metabolic pathways in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAGL plays a major role in the endocannabinoid metabolism in addition to its lipolytic functions. MAGL provides a large pool of arachidonic acid (AA), from which pro-inflammatory prostaglandins are generated 41 . 2-AG, CB1/CB2 receptors and MAGL are key regulators of the endocannabinoid system involve in regulation of various metabolic pathways in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…2-AG, CB1/CB2 receptors and MAGL are key regulators of the endocannabinoid system involve in regulation of various metabolic pathways in vivo. By inhibiting MAGL, 2-AG levels are increased in tumor cells and in tumor niches, leading to changes in immune cell behavior in the TME and resulting in altered immune cell profile within the tumor niches being shifted from pro-inflammatory profile to a more anti-tumorigenic profile 41 . The effects of 2-AG on immune cells and TME usually involve CB2 cannabinoid receptors, although CB1 independent effects such as leukotriene biosynthesis and LTB4 activation could be observed 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies revealed that MAGL promotes metastasis in nasopharyngeal carcinoma and lung cells. 37,38 Our study showed that in men with recurrent PCa tumor relapse, decreasing level of monoacylglycerols potentially leads to accelerating motility of highly metastatic cells because of overexpressing MAGL. Meanwhile, monoacylglycerols are formed biochemically via releasing fatty acids of diacylglycerol and triacylglycerol through MAGL.…”
Section: Ldtd-apci-ms-based Urinary Metabolomic Fingerprint By Untarg...mentioning
confidence: 82%
“…The monoacylglycerols portions of urine show a lower intensity in recurred patients, which may be associated with a function of glycerol lipase. 36,37 Glycerol lipase are active mediators involved in intricate biological processes closely associated with the pathological development of cancers. Lipids metabolites initiate from the synthesis of monoacylglycerols, followed by the storage within tissue and cells, and undergo lipolysis, which is regulated by corresponding lipases.…”
Section: Ldtd-apci-ms-based Urinary Metabolomic Fingerprint By Untarg...mentioning
confidence: 99%